An investigation into the aerospace industry with specific reference to the aero-engine sector and its electronic advancements - Gale, James William (2006)
This investigation initially analyses the general trends seen within the core sectors of the aerospace industry. The external macro environment and the external industry environment are then assessed using the relevant models and processes that have been presented within the literature, with specific reference to the United Kingdom. In order to develop a focused and detailed understanding of an aero-engine manufacturer's internal environment, a case-study Rolls-Royce is incorporated. Recent technological developments seen within the complex aero-engine are examined, with specific reference to electronics and the integration of the processes provided by Data Systems and Solutions. The overall benefit derived from investment in these core areas is assessed and examined in detail.